Physiology and pathology of extracellular vesicules - M. A. Panteleev; A. A. Abaeva; D. Yu. Nechipurenko; S. I. Obydenniy; A. N. Sveshnikova; A. M. Shibeko (Онкогематология)
This year marks the 50th anniversary of the first publication about blood plasma microparticles. Initially considered as cell fragments or “platelet dust”, extracellular vesicles currently attracted the attention of biochemists, biophysicists, physicians, pharmacists around the world. They are heterogeneous in structure and derived from many cell types, express different antigen and contain variety of biomolecules that determines wide range of biological activity, including procoagulant, regenerative, immunomodulating, and others. They play an important role in the pathophysiology of different diseases and conditions – from infarction, injuries and pregnancies to the “graft versus host” disease. The vesicles as medicaments and their carriers, as well as the drugs that affect them, are a rapidly developing field of research.